Encapsulating Semiconductor Quantum Dots in Supramolecular Metal‐Organic Frameworks for Superior Photocatalytic Hydrogen Evolution. Issue 1 (25th November 2021) - Pan, Chen; Chao, Jinyu; Niu, Fushuang; Xie, Songhai; Gu, Haoyang; Su, Tianhui; Hu, Ke; Zhang, Dan‐Wei; Liu, Ke; Liu, Guangfeng; Xie, Tengfeng; Li, Zhan‐Ting; et al.
Abstract: Solar‐to‐hydrogen conversion is a sustainable way of producing renewable fuels, yet the efficiency is limited by the poor photo‐induced charge‐carrier separation on electrode surface. Developing active and stable hydrogen evolution photocatalysts is challenging and entails intelligent material structure design and tailoring. Here, a novel water dispersible supramolecular metal organic framework (SMOF) is employed as a general and high‐performance platform to encapsulate CdS quantum dots (QDs) for achieving highly improved solar‐induced H2 ‐production activity. Particularly, the CdS QDs@SMOF heterostructure exhibits an excellent H2 generation activity of 49.4 µ mol h −1 (TOF = 47.0/h), exceeding those of most reported heterogeneous metal organic frameworks‐based photocatalytic systems. Advanced characterizations disclose that the strong electrostatic interaction and light‐induced charge transfer between SMOF and CdS QDs, combined with the high surface area, water dispersible nature, and abundant reactive centers synergistically contribute to this distinguished photocatalytic performance. The work not only demonstrates the water dispersible SMOF can serve as a versatile and effective platform supporting semiconductor to boost the photocatalytic H2 ‐production performance without co‐catalysts, but also paves avenues to the design and synthesis of SMOF‐based heterostructures for general catalysis applications. Abstract : A novel water‐dispersible supramolecular metal organic framework (SMOF) as a general and high‐performance platform to encapsulate semiconductor quantum dots (QDs) for achieving highly improved solar‐induced H2 production is demonstrated. In particular, CdS QDs@SMOF hybrid exhibits an excellent photocatalytic H2 evolving rate of 49.4 µmol h −1 with a TOF of 47.0/h, exceeding those of most reported heterogeneous MOF‐based photocatalytic systems.